Neuropathological Diagnostic Considerations in Hyperkinetic Movement Disorders - Den Dunnen, Wilfred (Frontiers in Neurology, 2013)
Neuropathology of hyperkinetic movement disorders can be very challenging. This paper starts with basic functional anatomy of the basal ganglia in order to appreciate that focal lesions like for instance tumor or infarction can cause hyperkinetic movement disorders like (hemi)ballism. The neuropathology of different causes of chorea (amongst others Huntington’s disease, neuroacanthosis, and HLD-2) and dystonia (DYT1, PD, and Dopa-Responsive Dystonia) are described. Besides the functional anatomy of the basal ganglia a wider anatomical network view is provided. This forms the basis for the overview of the neuropathology of different forms of tremor.